Udział produktów rolno-spożywczych w polskim handlu zagranicznym - Heller, Janusz; Kotliński, Kamil (Share of Agricultural and Food Products in Polish Foreign Trade, 2005)
A significant increase of demand for Polish food has many reasons. Among the most synthetic and general conditions of that fact one can find our access to the European Union. Thanks to the process of integration with the EU we were 'forced' to realize many investments which enhanced the quality of life. Liberalization of the rules regulating the foreign trade also had a positive influence on exports increase. Lower prices of Polish food is another factor intesifying the demand. It should be emphasized that all the positive tendencies were visible in the year prior to our formal access to the EU. Analysis and research of this subject in the following years will for sure confirm the results achieved in the year 2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 332-336